Optimized OPEP Force Field for Simulation of Crowded Protein Solutions - Timr, Stepan; Melchionna, Simone; Derreumaux, Philippe; Sterpone, Fabio (The journal of physical chemistry. B, 2023)
Macromolecular crowding has profound effects on the mobility of proteins, with strong implications on the rates of intracellular processes. To describe the dynamics of crowded environments, detailed molecular models are needed, capturing the structures and interactions arising in the crowded system. In this work, we present OPEPv7, which is a coarse-grained force field at amino-acid resolution, suited for rigid-body simulations of the structure and dynamics of crowded solutions formed by globular proteins. Using the OPEP protein model as a starting point, we have refined the intermolecular interactions to match the experimentally observed dynamical slowdown caused by crowding. The resulting force field successfully reproduces the diffusion slowdown in homogeneous and heterogeneous protein solutions at different crowding conditions. Coupled with the lattice Boltzmann technique, it allows the study of dynamical phenomena in protein assemblies and opens the way for the in silico rheology of protein solutions.
Keywords: Proteins; Computer Simulation; simulace molekulární dynamiky; roztoky; počítačová simulace; proteiny; Molecular Dynamics Simulation; Solutions